Medical fitness to drive in the EU with special reference to the age factor - Kereszty Éva Margit; Julesz Máté (2018)
As a general rule, Annex III of Directive 2006/126/EC of the European Parliament and of the Council on driving licences, does not impose an obligation on drivers to pass an examination of medical fitness to drive in order to obtain a driving licence. According to the EU Directive, EU member States are free to determine the rules of examination of medical fitness to drive. This freedom results in different regulations in different EU countries. In Hungary, the driver's family physician is allowed to assess medical fitness to drive. This also holds true in the Netherlands but in the Dutch legal system it is only the assessment that is incumbent on the family physician, whilst the permission is accorded by the Central Agency of Fitness to Drive Permission. In Hungary, the certification of medical fitness to drive is issued by the driver's family physician although the driving licence is issued by the Government Office. In Austria, medical fitness to drive is assessed by a contracted specialised doctor, who must be contracted by the Government Office for a term of 5 years and who has passed a medical officer's qualification examination but must not be the driver's family physician. This restriction applies in France as well. In complicated cases, the public health officer has the final word. An interesting parallel is to be found in the regulations of Hungary, Austria, France and the Netherlands: the doctor's remuneration is not covered by social security. With slight differences, the amount of the fee is similar in all the countries under examination. This fee is to be paid by the driver, meaning that the state does not consider the right to drive as a human right. This is the case despite the fact that many people drive their cars to earn their living.
Keywords: Egészségtudományok